Mapping Functional Connectivity in the Rodent Brain Using Electric-Stimulation fMRI. - Pérez-Cervera, Laura; Caramés-Tejedor, José María; Fernández-Mollá, Luis Miguel; Moreno, Andrea; Fernández, Begoña; Pérez-Montoyo, Elena; Moratal, David; Canals-Gamoneda, Santiago; Pacheco-Torres, Jesús (Springer Nature, 2018)
Since its discovery in the early 90s, BOLD signal-based functional Magnetic Resonance Imaging (fMRI) has become a fundamental technique for the study of brain activity in basic and clinical research. Functional MRI signals provide an indirect but robust and quantitative readout of brain activity through the tight coupling between cerebral blood flow and neuronal activation, the so-called neurovascular coupling. Combined with experimental techniques only available in animal models, such as intracerebral micro- stimulation, optogenetics or pharmacogenetics, provides a powerful framework to investigate the impact of specific circuit manipulations on overall brain dynamics. The purpose of this chapter is to provide a comprehensive protocol to measure brain activity using fMRI with intracerebral electric micro-stimulation in murine models. Preclinical research (especially in rodents) opens the door to very sophisticated and informative experiments, but at the same time imposes important constrains (i.e., anesthetics, translatability), some of which will be addressed here.
Política de acceso abierto tomada de: https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Resonancia magnética nuclear (Medicina) - Modelos animales; Bold; Intracerebral micro-stimulation; Preclinical MRI